Composition of carbopol 940 and HPMC affects antibacterial activity of beluntas (Pluchea indica (L.)) leaves extract gel - Fitra Alvionida; Nanik Sulistyani; Nining Sugihartini (Universitas Ahmad Dahlan, 2021)
Indonesia is a country known for its source of biological wealth, one of which is beluntas leaves. Beluntas leaves have the potential to be an antibacterial, so it is appropriate to be formulated in the form of medicinal preparations, especially gels. This study aims to find out the influence of variations between carbopol gel base 940 and Methylcellulose Hydroxypropyl (HPMC) on the physical properties of gel preparations beluntas leaf extract (Pluchea indica (L.), and know the influence of gel of extract of beluntas leaves on antibacterial activity. The extract is obtained by the maceration method using ethanol solvent 96%. Each formula uses 15% of the extract of beluntas leaves. Gels are made in four gel base variations namely F0 (0.5% carbopol, 1% HPMC), FI (1% carbopol, 1.5% HPMC), FII (1.5% carbopol, 2.5% HPMC), and FIII (2% carbopol, 3% HPMC). Gels evaluated for their physical properties include organoleptic, viscosity, pH, homogeneity, scattering power, adhesion and Freeze-thaw cycling. Then the gel tested antibacterial activity against bacteria Staphylococcus aureus and Pseudomonas aeruginosa by cup-plate diffusion method. The data obtained were analyzed with One Way Anova and LSD with a 95% confidence level. The results showed that beluntas leaf extract gel meets the organoleptic requirements, homogeneity, good gel adhesion (> 4sec), good gel viscosity (2000-50.000 cps), and good gel pH (4.5-6.5). However, the gel does not meet the requirements of good scattering power (5-7 cm) and Freeze-thaw cycling. Based on the test results that have been done with some of the parameters above, The best composition of carbopol 940 and HPMC in the beluntas leaf extract gel which has antibacterial activity against Staphylococcus aureus and Pseudomonas aeruginosa Â is 1% carbopol and 1.5% HPMC. The antibacterial activity of the formula is categorized as strong.